The Effect of Bacteria in Thermal Comfort in Building: A Systematic Review - Aisa, Sharifuddin; Juki, Mohd Irwan (Recent Trends in Civil Engineering and Built Environment, 2023)
Bacteria is widely used in concrete as self-healing agent this is called bio-concrete, this production might affect the thermal comfort in the building. The aims of this study are to investigate the effect of bacteria in thermal comfort of building and to identify the factors that affect the thermal comfort in building. The comparison surprisingly showed that the presence of bacteria in concrete can enhance the compressive strength of concrete and the durability. Suitable type of bacteria used and compressive strength is chosen from the review that often been used by the researchers. The outcomes of this research demonstrate the different usage of bacteria has different effect on concrete, which can lead to increase the compressive strength of concrete and its durability.